Munâsabat al-Nuṣuṣ baina Kitab al-Muṭâla’ah al-Juz al-Awwal wa kitâb al-Lughah al-‘Arabiyyah li al-Mustawa al-Mubtadi’i Taḥta Naẓariyyah Rushdi Aḥmad Ṭu’aimah - Nur Hidayatun Na'imah; Syafi’i (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
Purpose- This research focuses on examining the text of Mutholaah book part 1 by Mahmud Yunus with the theory of Arabic textbooks as seen through Rusydi Ahmad Thuaimah.   Design/Methodology/Approach- The researcher applied a qualitative approach with the literature study method. The data used in this study is the content of Mutholaah book part 1 by Mahmud Yunus and the theory of Arabic textbooks as a language learning book from the perspective of Rusydi Ahmad Thuaimah. Findings— The results illustrated that the content of Mutholaah book part 1 according to the theory of Arabic textbooks as a language learning book from the perspective of Rusydi Ahmad Thuaimah is evidenced by the presentation of relevant, light, and weighty material starting from voccabularies, tenses, and reading text. Research Limitation/Implications- The researcher encountered problems in reviewing the theoretical points of the Arabic language learning book from the perspective of Rusydi Ahmad Thuaimah in Mutholaah book part 1, however, the researcher was able to solve it by literature study through several relevant books and journals.